Manajemen Pembiayaan Pendidikan dan Implikasinya Dalam Meningkatkan Mutu Pendidikan - Syofan Syofian; Nuraini Asriati (Journal on Education, 2024)
This research aims to analyze the fundamental concepts of education financing management and its implications for improving the quality of education. The study uses a literature review method. The findings indicate that improving the quality of educational institutions is a hope and desire of the community, particularly the users of educational services. Therefore, to achieve this, various strategic efforts have been made by the government and the community as managers and stakeholders in education. For instance, the government has designed national education standards. According to Law No. 20 of 2003, there are eight national standards aimed at improving the quality of educational institutions. Based on government regulations, one of the eight national education standards is the standard for financing. Education financing is crucial and inseparable from the management of education. Among the government's policies is the distribution of BOS funds at the school level. The financing and funding managed by schools/madrasahs must be transparent to ensure accountability. If it can be accounted for, the credibility of the educational institution will also increase. If it is credible, this will naturally enhance the quality of the institution